ANALISIS PERBEDAAN KINERJA PERUSAHAAN SEBELUM DAN SAAT PANDEMI COVID-19 - Hilman, Cindy; Laturette, Kazia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2021)
This study aims to determine differences in the performance of the profitability ratio (ROA), sales growth ratio (SG), liquidity ratio (CR) and leverage ratio (DER) to bankruptcy prediction (Altman Z-score) before and during the Covid 19 pandemic. Descriptive statistical method with secondary data collection, namely quarterly financial reports from 2019-2020. Samples were taken by purposive sampling method and obtained 62 samples of the construction industry and consumer goods in 2019-2020. Normality testing using the Kolmogorov-Smirnov test results in data not normally distributed with a significance value below 0.05. Different tests using the non-parametric Wilcoxon sign test resulted in differences in ROA (0.000 <0.05), SG (0.004 <0.05) and CR (0.005 <0.05) on the decreased bankruptcy predictions during the pandemic. Meanwhile, DER (0.803 <0.05) did not differ from the prediction of bankruptcy before and during the COVID-19 pandemic